2015
DOI: 10.1007/s10238-015-0358-1
|View full text |Cite
|
Sign up to set email alerts
|

Decreased microRNA miR-181c expression in peripheral blood mononuclear cells correlates with elevated serum levels of IL-7 and IL-17 in patients with myasthenia gravis

Abstract: miR-181c is a newly identified negative regulator of immune cell activation. In this study, we aimed to investigate the expression and functional role of miR-181c in myasthenia gravis (MG). miR-181c showed significant downregulation in peripheral blood mononuclear cells (PBMCs) from MG patients compared with healthy controls, with lower expression in generalized patients than in ocular ones. MG patients also had increased serum IL-7 and IL-17 levels. Additionally, serum IL-7 level presents a positive correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…miR‐181c participates in several biological pathways including tumorgenesis, inflammation, nervous and immune system development, and the tissue differentiation . However, its effect on renal function is not well elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…miR‐181c participates in several biological pathways including tumorgenesis, inflammation, nervous and immune system development, and the tissue differentiation . However, its effect on renal function is not well elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Our current study, for the first time, demonstrated that miR-181c dramatically ameliorated CsA-induced renal injury by improvement of renal fibrosis through inhibiting EMT. miR-181c participates in several biological pathways including tumorgenesis, inflammation, nervous and immune system development, and the tissue differentiation [18][19][20][21][22]. However, its effect on renal function is not well elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…As of now, most T-cell intrinsic miRNAs that regulate Th17/Treg balance were found during the development and progression of MS and EAE. Although miR-20b, 22 miR-30a, 23 miR-146a, 24 miR-214 25 and miR-26a 26 were down-regulated in CD4 + T cells or Th17 cells during the process of demyelination disease in both patients with MS and EAE mice, the expression of miR-17-92, 27 miR-326, 28 miR-384, 29 miR-181c, 30 miR-21, 31 miR-132/212, 32 miR-155, 33 miR-27a, 25 miR-590, 34 miR-448, 35 miR-141, 36 miR-200a 36 and miR-223 37 was markedly increased. As a consequence, the dysregulation of these miRNAs contributes to the increased Th17 response.…”
Section: T-cell Intrinsic Mirnasmentioning
confidence: 95%
“…Inhibition of miR-146a was found to reduce cell surface costimulatory molecules, such as CD40, CD80, CD86 and intracellular TLR4 and NF-κB levels in AChR-specific B cells (6). miR-181c was found to negatively regulate the production of pro-inflammatory cytokines interleukin-7 (IL-7) and IL-17 (7). Recently, as new potential therapeutic targets, miRNAs have attracted increased interest (8).…”
Section: Introductionmentioning
confidence: 99%